Effect on the Structure in Elevation of Wood Deterioration on Small-Pile Foundation: Numerical Analyses. Issue 1 (2nd January 2016) - Bettiol, Giulia; Ceccato, Francesca; Pigouni, Aikaterina Evina; Modena, Claudio; Simonini, Paolo
ABSTRACT: Wooden pile foundations are quite common in Venice historical building. Very short, small-diameter piles are embedded into the soft shallowest soil layer under the groundwater level, but wood degradation is not prevented as anaerobic bacteria can flourish even in anoxic condition. This study couples the behavior of the masonry structure and the foundation as result of pile degradation. The numerical analyses, relative to the ancient piling, consider wood decay and secondary settlement of soil. The effect of deterioration as a function of the pile spacing and the possible presence of a stiff layer under pile tips are also investigated. The geotechnical results are then used as input for the structural model. The behavior of the masonry as result of different states of wood conservation along the wall is studied numerically.